Pengaruh Kepuasan Dan Loyalitas Pelanggan Terhadap Keputusan Menggunakan Jasa Layanan Ojek Online Di Wilayah Eks Karesidenan Surakarta - Cahya Gumilang, Bintang, Muzakar Isa, S.E, M.Si (2017)
The progress of business nowadays are really fast either product or service,so it need the right strategies for marketing to face competition in business and maintain what we already have or even increasing the amount of costumer. Like in the business of motorcycle online services which recently discussed by many party for its existence. There are many things that influenced consumers to use a motorcycle online services, amongst them is the satisfaction and customer loyalty. This study aimed to analyze the effect of satisfaction and customer loyalty in partial and simultaneously to the decision to use the services of motorcycle online services. This research using survey method with the population of the research are the all costumers of motorcycle online services, the sample that taken are 100 respondents by using purposive sampling with criteria that the respondent already had the experience of using the motorcycle online sevices. The methods that used for analyzing the data are test instrument of research (test validity and reability), test the classic assumption, (normality test and multicollinearity), test multiple linear regression, and test Godness of Fit (t test, F test and the coefficient of determination/ R2). The results showed customer satisfaction significant positive effect on consumer purchasing decisions, meaning that the higher level of customer satisfaction, the higher the subsequent purchasing decisions. Consumer loyalty significant positive effect on repurchase decisions, meaning that the higher level of consumer loyalty, the higher the subsequent purchasing decisions. Satisfaction and customer loyalty significantly influence the purchasing decision back, meaning jointly satisfaction and loyalty significantly influence the purchasing decision back. Keywords: Satisfaction, Loyalty, Purchasing Decisions.